Using Contingent Valuation in the Design of Payments for Environmental Services Mechanisms : A Review and Assessment - Whittington, Dale; Pagiola, Stefano (World Bank, Washington, DC, 2014)
As the use of payments for environmental services (PES) programs for conservation has grown in developing countries, the use of stated preference methods, particularly contingent valuation (CV) surveys, to estimate the maximum amount that users of environmental services (buyers) would be willing to pay has also increased. This paper reviews 25 CV studies conducted in the context of PES programs (CV-PES) and assesses their quality and usefulness for designing PES programs. Almost all these studies attempt to estimate the demand of downstream water users for up-stream watershed protection and, more generally, for improved water services. Most studies were methodologically uninspired and generally low-quality applications of stated preference methods, with limited policy relevance. The quality and usefulness of CV-PES studies could be substantially improved at only a modest increase in costs.